Human Resources of Lithuania: On the Question of the Fate of the Nation - Vaitekūnas, Stasys (Bulletin of Geography. Socio-economic Series, 2008)
The mutual dependence of human resources and the development of the state has been one of the most important geopolitical questions discussed from the times of Ancient Greece. The article analyses the growth of the population and human resources of Lithuania, their change and influence on the state's development, the possible consequences of the decline of the population on international policies and the state's geopolitical situation. Reflecting the changes in the number of inhabitants and their structure five possible scenarios of the state's development in the future are constructed: 1) a small, but economically strong national state; 2) more pensioners than grandchildren; 3) a multinational and multicultural state; 4) the end of the national state (?); 5) a strong economic and cultural state.